2012
DOI: 10.1063/1.4769368
|View full text |Cite
|
Sign up to set email alerts
|

Electric field-induced tetragonal to orthorhombic phase transitions in [110]c-oriented BaTiO3 single crystals

Abstract: Electric field-induced phase transitions in [110]c-oriented BaTiO3 single crystals were studied by macroscopic electrical measurements in the temperature range from 20 °C to 50 °C. Discontinuous, hysteretic jumps in the polarization and strain were observed, indicating a tetragonal ↔ orthorhombic phase transition. The critical electric field to induce the transition was found to shift to higher values with increasing temperature. The Landau-Devonshire theory was used to analyze the observed electric field-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…Paper orthorhombic phase, which is consistent with the phenomenon in large grains [45,46]. From Fig.…”
Section: Originalsupporting
confidence: 85%
“…Paper orthorhombic phase, which is consistent with the phenomenon in large grains [45,46]. From Fig.…”
Section: Originalsupporting
confidence: 85%
“…Alternatively, it may also be possible that bias induced color change is associated with the (electric) field induced structural change [27] of the molecule which may lead to band gap variation and hence change in optical properties [28]. To discount this effect control experiment was done by sandwiching viologen between two quartz substrates without the ITO electrode.…”
Section: Resultsmentioning
confidence: 99%
“…The field-induced phase transitions in single domain ferroelectrics can be described with the phenomenological Landau theory in terms of the order parameter polarization [22, 23, 25]. The Devonshire form of the free energy density is given by where α , γ and δ are the reciprocal dielectric susceptibility and the higher-order dielectric stiffnesses at constant electric field, P are the components of polarization, ε is the strain tensor, E is the applied electric field and q are the cubic electrostrictive coefficients [55].…”
Section: Resultsmentioning
confidence: 99%
“…Following the work of Bell [23, 24] and Franzbach et al [25] a thermodynamic analysis was presented, which suggested that stress-induced phase transitions could be responsible for the observed behavior. Similar observations of the stress-dependent shift in phase of perovskite ferroelectrics have been previously presented, where mismatch strains were found to significantly shift the phase transition temperature, induce new phases and change the order of the transition in thin films [2628] and in bulk materials [2931].…”
Section: Introductionmentioning
confidence: 99%